Treatment of infantile fibrosarcoma: A tertiary care center experience - Han, Yidi; Lian, Kai; Zhang, Dongdong (Frontiers in Pediatrics, 2022)
Objective: Infantile fibrosarcoma (IFS) is a highly locally aggressive nonrhabdomyosarcomatous soft tissue sarcoma that most commonly occurs in young infants. There exists no standard treatment this lesion due to its rarity. We shared our treatment experience for IFS in this study. Methods: Patients’ record between January 2013 and December 2018 were reviewed and patients with newly diagnosed IFS were included. The clinical characteristics, treatment strategy, treatment-related toxicities and clinical outcome were retrospectively analyzed. Results: Eleven patients were admitted in our center, including 4 girls and 7 boys, and the median age at diagnosis was 5 months (range 1-23 months). Ten patients achieved complete remission (CR) after the completion of initial treatment. The main short-term adverse effects was myelosuppression. Three patients experienced relapse, including two patients with local progression and one patient with distant metastasis. After a median follow-up of 3.5 years (range 1.5-7 years) , 9 patients were alive and 2 patients died. The 3-year overall survival (OS) rate was 93.5% (95% CI 83.7-98.2). Conclusion: We formulated the treatment strategy according to group grade and the experience from previous studies, which may be effective and feasible for the treatment of IFS. Keywords: Infantile fibrosarcoma, Infant, Intergroup Rhabdomyosarcoma Study Group, Non-mutilating surgical resection, Chemotherapy.